The impact of FinTech literacy on digital entrepreneurial intentions: Exploring crowdfunding, blockchain, and AI through a social cognitive career theory lens - Sy Long Pham; Anh Duc Do; Dieu Linh Ha; Mai Van Trinh; Anh Duc Le; Thi Phuong Hien Tran (Entrepreneurial Business and Economics Review)
Objective: The objective of the article is to investigate the association between FinTech literacy and the intention to become digital entrepreneurs utilizing the social cognitive career theory (SCCT). Specifically, it sheds light on how three aspects of FinTech literacy (crowdfunding, blockchain, and artificial intelligence) influence individuals’ digital entrepreneurial self-efficacy and outcome expectations. Additionally, it examines the separate and sequential mediation roles of digital entrepreneurial self-efficacy and outcome expectations in the connection between literacy in crowdfunding, blockchain, and AI and digital entrepreneurial intention.